2009
DOI: 10.2147/opth.s4853
|View full text |Cite
|
Sign up to set email alerts
|

Role of fixed-combination brinzolamide 1%/timolol 0.5% in the treatment of elevated intraocular pressure in open-angle glaucoma and ocular hypertension

Abstract: Brinzolamide 1%/timolol 0.5% is a new fixed-combination for the treatment of open-angle glaucoma or ocular hypertension. Brinzolamide/timolol has a favorable safety profile, with an incidence of ocular burning and stinging <5%. Published data show that brinzolamide 1%/timolol 0.5% and dorzolamide 2%/timolol 0.5% have similar efficacies for lowering intraocular pressure (IOP). There is some evidence that brinzolamide/timolol may be more comfortable. Although patients receiving brinzolamide/timolol may experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…Other studies measuring BT efficacy alone showed similar efficacy to that of DT reported in the earlier literature. [ 14 15 16 ] However, in our study, we found that both BT and DT significantly reduced the IOP at all study visits, but there were lower mean IOPs for DT than BT at all study visits that was statistically significant at 2 weeks. There was also a statistically significant higher percentage of IOPs reduction with DT than BT at all study visits.…”
Section: Discussioncontrasting
confidence: 57%
“…Other studies measuring BT efficacy alone showed similar efficacy to that of DT reported in the earlier literature. [ 14 15 16 ] However, in our study, we found that both BT and DT significantly reduced the IOP at all study visits, but there were lower mean IOPs for DT than BT at all study visits that was statistically significant at 2 weeks. There was also a statistically significant higher percentage of IOPs reduction with DT than BT at all study visits.…”
Section: Discussioncontrasting
confidence: 57%
“…Reducing IOP is currently the only therapeutic approach effective in preventing progression of open-angle glaucoma and ocular hypertension 8,33. Topical ophthalmic pharmacotherapies are commonly employed to manage IOP in patients with these conditions 8.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing IOP is currently the only therapeutic approach effective in preventing progression of open-angle glaucoma and ocular hypertension. 8 , 33 Topical ophthalmic pharmacotherapies are commonly employed to manage IOP in patients with these conditions. 8 Chronic treatment with a single IOP-lowering agent is often insufficient to maintain IOP reduction in the long term; 10 , 11 as a result, concomitant pharmacotherapies may be required to achieve additional IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, a new fixed combination product, brinzolamide 1%/timolol 0.5% (Azarga; Alcon Laboratories, Inc., Fort Worth, TX), has been introduced and received regulatory approval by the European Medicines Agency in November 2008 for the treatment of patients. 3 Brinzolamide is a topical carbonic anhydrase inhibitor (CAI) that lowers IOP by decreasing aqueous humor secretion, whereas timolol is a beta-adrenergic blocking agent that reduces IOP by slowing the rate of aqueous humor formation. 4,5 In recent studies, the fixed combination of brinzolamide 1% and timolol 0.5% (FCBT) was found to be effective and well tolerated with less ocular discomfort and adverse effects.…”
Section: Introductionmentioning
confidence: 99%